Progressive pedagogical ideas in Lithuanian folk tales - Lazauskienė , M. (Psichologija, 1973)
Many folk tales compare and contrast the results of positive and negative upbringing in a family. The article deals with the main ideas of folk tales: victory of good against evil, love of work, collectivity and folk solidarity, anti-religious views upon nature and society, etc. ln folk educational practice the progressive ideas of tales were spontaneously passed over to children and formed their images and primary moral perceptions. By elevating positive qualities the folk tales indicated the direction for the development of personality. Examples are given to reveal the educational content of folk tales and their variety of pedagogical ideas.